Detection of Aflatoxin and Ochratoxin A in Spices by High-Performance Liquid Chromatography. (12th December 2020) - Zareshahrabadi, Zahra; Bahmyari, Robab; Nouraei, Hasti; Khodadadi, Hossein; Mehryar, Pouyan; Asadian, Fatemeh; Zomorodian, Kamiar
Abstract : Background . Spices are one of the flavoring components of food in the cooking recipes of different nations that are used daily. However, these ingredients may be contaminated by toxicogenic fungi and subsequent production of mycotoxins that cannot be neutralized through cooking. In the present study, the possible contamination of spices by aflatoxins (AFs) and ochratoxin A (OTA) was investigated from Shiraz, the south part of Iran. Materials and Methods . A total of 80 spice samples including turmeric ( n = 20), red pepper ( n = 20), black pepper ( n = 20), and cinnamon ( n = 20) were purchased from markets and cultured on appropriate medium. The isolated fungi were identified. Simultaneously, mycotoxins from spices were extracted with immunoaffinity columns (IAC) and the occurrence of AFs (B1 + B2 + G1 + G2) and OTA was then determined using high-performance liquid chromatography (HPLC) with a fluorescence detector (FD). Result . The results depicted that 40 spice samples were contaminated with AFs and 48 samples with OTA. The highest rate of AFs contamination was related to red pepper, in 80% of which the amount of contamination was excessive than the standard level (>10 μ g/kg). All black pepper samples were determined to be contaminated with OTA at over legislation limits of >15 μ g/kg. Aspergillus species were the predominant isolated fungi, followed by Penicillium, and Mucor species. Discussion . Regarding the high mycotoxins contamination in spices in the current study, regular effective surveillance and quality control procedures are highly recommended. To achieve this goal, it is necessary to empower food-related laboratories with precise methods of isolation and detection of mycotoxins.